2023
DOI: 10.3390/jof9020161
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Aspergillosis in Horses

Abstract: Invasive pulmonary aspergillosis (IPA) may be a rare cause of granulomatous pneumonia in horses. The mortality of IPA is almost 100%; direct diagnostic tools in horses are needed. Bronchoalveolar lavage fluid (BALF) and serum samples were collected from 18 horses, including individuals suffering from IPA (n = 1), equine asthma (EA, n = 12), and 5 healthy controls. Serum samples were collected from another 6 healthy controls. Samples of BALF (n = 18) were analyzed for Aspergillus spp. DNA, fungal galactomannan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
2
1
Order By: Relevance
“…Clinicians must take care in attributing significance to the presence of fungal elements, free or in large quantity, in transtracheal aspirate fluid, as they are commonly identified in healthy horses or horses with severe asthma (Dobiáš et al, 2023). The fungal elements found in the transtracheal lavage should not be considered clinically relevant whenever accompanied by a normal predominance of macrophages, lymphocytes, and nondegenerate neutrophils (Stewart & Cuming, 2015), contrasting with the findings of degenerated neutrophils found in this report.…”
Section: /8contrasting
confidence: 57%
See 2 more Smart Citations
“…Clinicians must take care in attributing significance to the presence of fungal elements, free or in large quantity, in transtracheal aspirate fluid, as they are commonly identified in healthy horses or horses with severe asthma (Dobiáš et al, 2023). The fungal elements found in the transtracheal lavage should not be considered clinically relevant whenever accompanied by a normal predominance of macrophages, lymphocytes, and nondegenerate neutrophils (Stewart & Cuming, 2015), contrasting with the findings of degenerated neutrophils found in this report.…”
Section: /8contrasting
confidence: 57%
“…One hypothesis for the development of pulmonary aspergillosis in the present report is the possibility that this fungal infection was facilitated by the clinical condition of asthma, as previously suspected in clinical examinations. Dobiáš et al (2023) demonstrated that the trachea could be massively colonized by Aspergillus species, especially in individuals with severe asthma. Both in this report and in that of Moreira et al (2004) it is likely that both animals presented a fungal pulmonary condition at the beginning of its evolution secondary to equine asthma.…”
Section: /8mentioning
confidence: 99%
See 1 more Smart Citation